Operando Study of Structure Degradation in Solid‐State Dye‐Sensitized Solar Cells with a TiO2 Photoanode Having Ordered Mesopore Arrays. Issue 9 (9th June 2022) - Li, Nian; Guo, Renjun; Oechsle, Anna Lena; Reus, Manuel A.; Liang, Suzhe; Song, Lin; Wang, Kun; Yang, Dan; Allegretti, Francesco; Kumar, Ajeet; Nuber, Matthias; Berger, Jan; et al.
Abstract : Via operando grazing‐incidence small‐angle X‐ray scattering, the degradation mechanisms of solid‐state dye‐sensitized solar cells (ssDSSCs) using two types of ordered mesoporous TiO2 scaffolds with different pore sizes, and an exemplary dye D205, are investigated. The temporal evolution of the inner morphology shows a strong impact on device performance. The photoinduced dye aggregation on the TiO2 surface leads to an increase in the domain radius but a decreased spatial order of the photoactive layer during the burn‐in stage. This dye aggregation on the TiO2 surface causes the short‐circuit current density loss, which plays a major role in the power conversion efficiency decay. Finally, it is found that a larger surface area in the small‐pore sample yields a faster short‐circuit current density decay as compared with the big‐pore sample. Therefore, a control of dye aggregation and the pore size of TiO2 photoelectrodes is crucial for the stability of TiO2 ‐based ssDSSCs. Abstract : Operando grazing‐incidence small‐angle X‐ray scattering of titania (TiO2 )‐based solid‐state dye‐sensitized solar cells (ssDSSCs) demonstrates dye aggregation at the TiO2 interface as the leading degradation mechanism causing the short‐circuit current density decay of the ssDSSCs. Smaller pores give rise to a faster degradation.